(untitled) (Bangladesh Journal of Pharmacology, 2015)
We investigated dose-dense weekly paclitaxel and carboplatin compared with conventional paclitaxel and carboplatin treatment on stage II-IV ovarian cancer patients. Between July, 2011, and October, 2014, a total of 221 patients was randomly assigned to receive dose-dense weekly paclitaxel and carboplatin group (n = 109) and conventional paclitaxel and carboplatin group (n = 112), just after the sixth chemotherapy cycles, and at 12 months after randomization. Median progression-free survival (PFS) was 16.8 months (range 3.3-48+ months) of conventional paclitaxel and carboplatin group was lower than that of dose-dense weekly paclitaxel and carboplatin group 27.6 months (range 4.2-51+ months). But, these clinical responses were not statistical significance in each group. In conclusion, dose-dense weekly paclitaxel and carboplatin treatment improves survival compared with conventional paclitaxel and carboplatin treatment.